Analisis Makna Pesan Moral Dalam Film “Jalan Yang Jauh, Jangan Lupa Pulang” (Analisis Semiotika Rholand Barthes) - Zahra, Farah Mutiara; Aulia, Mega Putri; Deti, Wilda Okta Dwina; Pratama, Sapta Wahyu; Admaika, Ilham Maulana (Peneliti.net, 2024)
Abstract : This research aims to determine the meaning of the moral message in the film Jalan Yang Jauh, Jangan Lupa Pulang using Rholand Barthes' semiotic analysis. This research uses qualitative research. Qualitative is a type of approach to understand the phenomena experienced by research subjects (behavior, perception, action, etc.), by describing them in the form of words and language that are easy to understand. The qualitative approach does not use statistical analysis procedures or other methods of quantification. The type of data used in this research is divided into two types, namely primary data and secondary data. And in this film the meaning of denotation, connotation and myth is produced which contains a moral message.